Systematic review of transpyloric versus gastric tube feeding for preterm infants. Issue 3 (21st April 2004) - McGuire, W; McEwan, P
Abstract : Aim: To determine if enteral tube feeding by the transpyloric versus the gastric route improves feeding tolerance, and growth and development, without increasing adverse events, in preterm infants. Methods: Systematic review of randomised controlled trials. A search was made of the Cochrane Controlled Trials Register (CCTR; 2003, issue 1), Medline (1966 to April 2003), and Embase (1980 to April 2003), and references in previous reviews. The data were extracted, analysed, and synthesised using the standard methods of the Cochrane Neonatal Collaborative Review Group. Results: Data were found from eight trials. No evidence of an effect on growth or development was found, but transpyloric feeding was associated with a greater incidence of gastrointestinal disturbance: relative risk (RR) 1.45, 95% confidence interval (CI) 1.05 to 2.09. Transpyloric feeding was also associated with increased mortality: RR 2.46, 95% CI 1.36 to 4.46. However, the trial that contributed most to this finding may have been affected by allocation bias. No significant differences were detected in the incidence of other adverse events, including necrotising enterocolitis, intestinal perforation, and aspiration pneumonia. Conclusions: No evidence of benefit was found, but evidence of harm was found. Feeding by the transpyloric route cannot be recommended for preterm infants.